Activated IL-1RI Signaling Pathway Induces Th17 Cell Differentiation via Interferon Regulatory Factor 4 Signaling in Patients with Relapsing-Remitting Multiple Sclerosis - Sha, Yonggang; Markovic-Plese, Silva (Frontiers in Immunology, 2016)
IL-1β plays a crucial role in the differentiation of human Th17 cells. We report here that IL-1RI expression is significantly increased in both naïve and memory CD4+ T cells derived from RR MS patients in comparison to healthy controls (HCs). IL-1RI expression is up-regulated in the in-vitro differentiated Th17 cells from RRMS patients in comparison to the Th1 and Th2 cell subsets, indicating the role of IL-1R signaling in the Th17 cell differentiation in RR MS. When IL-1RI gene expression was silenced using siRNA, human naïve CD4+ T cells cultured in the presence of Th17-polarizing cytokines had a significantly decreased expression of IRF4, RORC, IL-17A, IL-17F, IL-21, IL-22 and IL-23R genes, confirming that IL-1RI signaling induces Th17 cell differentiation. Since IL-1R gene expression silencing inhibited IRF4 expression and Th17 differentiation, and IRF4 gene expression silencing inhibited Th17 cell differentiation, our results indicate that IL-1RI induces human Th17 cell differentiation in an IRF4-dependant manner. Our study has identified that IL-1RI-mediated signaling pathway is constitutively activated, leading to an increased Th17 cell differentiation in IRF4-dependent manner in patients with RR MS.